(untitled) (Research, Society and Development, 2020)
Until the mid-2000s, there was a specific failure in Brazil to collect very strong taxes, which is called tax evasion (or tax evasion). To correct the gap and integrate taxpayer data with municipal, state and federal tax authorities, SPED (Public Digital Bookkeeping System) was implemented through a national agreement of the tax authorities, thus promoting the sharing of accounting and tax information. The Electronic Invoice (NF-e) one of the tools of SPED and object of study of this research, aims to legalize an operation of circulation of goods or services, performing the simplification of the processes required by law, thus seeking uniformity and precision in the information transmitted to the tax authorities. In this way, the present work presents a research about the structure of SPED and the degree of competence of those involved in issuing the NF-e. The methodological approach used was a bibliographic review to legitimize the development of the study, followed by an exploratory research that follows standardized models of investigation. Data collection was carried out by means of an objective questionnaire, personally delivered to 40 companies in the trade branch in the City of Marabá - PA, which had the purpose of showing if the invoice was being correctly issued. As a conclusion, the description of the entire NF-e processing, the degree of knowledge of those involved in the NF-e issue, and the importance of companies to implement periodic and in-depth training on SPED are highlighted.